Nuclear receptor 4A (NR4A) family – orphans no more. Issue 157 (March 2016) - Safe, Stephen; Jin, Un-Ho; Morpurgo, Benjamin; Abudayyeh, Ala; Singh, Mandip; Tjalkens, Ronald B.
Highlights: NR4A receptors play a critical role in maintaining cellular homeostasis. NR4A receptors also play critical roles in multiple diseases. Ligands for NR4A receptors have been characterized. NR4A ligands have applications for treating multiple diseases and cancer. Abstract: The orphan nuclear receptors NR4A1, NR4A2 and NR4A3 are immediate early genes induced by multiple stressors, and the NR4A receptors play an important role in maintaining cellular homeostasis and disease. There is increasing evidence for the role of these receptors in metabolic, cardiovascular and neurological functions and also in inflammation and inflammatory diseases and in immune functions and cancer. Despite the similarities of NR4A1, NR4A2 and NR4A3 and their interactions with common cis -genomic elements, they exhibit unique activities and cell-/tissue-specific functions. Although endogenous ligands for NR4A receptors have not been identified, there is increasing evidence that structurally-diverse synthetic molecules can directly interact with the ligand binding domain of NR4A1 and act as agonists or antagonists, and ligands for NR4A2 and NR4A3 have also been identified. Since NR4A receptors are key factors in multiple diseases, there are opportunities for the future development of NR4A ligands for clinical applications in treating multiple health problems including metabolic, neurologic and cardiovascular diseases, other inflammatory conditions, and cancer.